Digitizing AJN - &NA (AJN, American Journal of Nursing, 2006)
BACKGROUND: Transradial access (TRA) is a standard approach to cardiac catheterization. Following the procedure, air-filled compression bands are often used to achieve hemostasis at the access site. Despite research supporting early, gradual deflation to minimize complications, there is no established best practice for band deflation. At our urban academic medical center, the lack of a standardized compression band deflation protocol resulted in varied start times and amounts of air removed with each attempt, as well as inconsistent documentation. PURPOSE: The aim of this quality improvement project was to develop and implement an evidence-based practice (EBP) initiative to standardize TR compression band deflation and documentation. METHODS: Nurses, who were primarily responsible for the TRA procedure, organized a multidisciplinary team to critically evaluate the literature, identify gaps in clinical practice, and develop and implement a practice change. EBP interventions centered on a TR compression band deflation algorithm that included specified wait times based on the procedure type and anticoagulation received and the criteria for reinserting air based on bleeding status. A standardized documentation process was also instituted. Deflation was initiated at 30 minutes for patients undergoing diagnostic procedures or receiving up to 5,000 units of heparin and at 60 minutes for patients undergoing advanced diagnostic procedures or percutaneous coronary intervention (PCI) and receiving more than 5,000 units of heparin or IV bivalirudin. Demographics, documentation, complications, time to remove the compression band, length of stay (LOS), patient satisfaction, and opportunity benefit were analyzed. RESULTS: The preintervention (n = 214) and postintervention (n = 255) groups were comparable in age, gender distribution, procedure type, and anticoagulant use. Following the rollout of the EBP initiative, there was a statistically significant reduction in the time required for successful compression band removal for both diagnostic procedures (P < 0.001) and PCIs (P < 0.001). LOS decreased across all procedure types. Specifically, diagnostic procedures had a statistically significant postintervention reduction in LOS (P < 0.001). In addition, clinical documentation (encompassing air removed, air reinserted, and complications) showed significant postintervention improvement (P < 0.001). Regarding safety outcomes, over 85% of patients in the postintervention group experienced no recorded complications during band removal, while 100% had no major bleeds or hematomas. CONCLUSIONS: This EBP initiative confirms that an early band deflation algorithm reduces time for band removal and LOS across diagnostic, advanced diagnostic, and PCI procedures without compromising patient safety. Furthermore, the initiative improved documentation, ensuring consistent monitoring and nursing transitions. These findings provide a clinical basis for adopting early compression band deflation for TRA procedures.